Mirza Ghulam Ahmad: Founder of the Ahmadiyya Muslim from Qadian, India - Sofianto, Kunto (TAWARIKH, 2016)
ABSTRACT: This writing discusses the background of Mirza Ghulam Ahmad founded AhmadiyyaÂ  and the response of Indian people at that time. Ahmadiyya was founded by Mirza Ghulam Ahmad in the city of Ludhiana, India, in 1889. He was born on 13th February 1835 in Qadian, India, and died in the city of Lahore, India, on 26th May 1908. At the end of 1890, Mirza Ghulam Ahmad claimed to be âImam Mahdiâ and âAl-Masihâ (Messiah) promised by the Prophet Muhammad to revive Islam and enforcing Islamic law at the end of time. Recognition of Mirza Ghulam Ahmad as âImam Mahdiâ and Messiah is a revelation which he admits received from God, as well as the âProphetâ (for Qadianism) and âMujaddidâ (for Lahoreism) is the core ideology of Ahmadiyya. At the beginning of his activities in India, Mirza Ghulam Ahmad was accepted by the Muslims in general as âmujaddidâ. However, after he claimed to receive revelations and had been appointed by God as the âMahdiâ and Messiah, and even claimed to be a âProphetâ, then, many Muslims opposed it. The ulemas in India also imposed infidel to Mirza Ghulam Ahmad and his followers. Mirza Ghulam Ahmad and his followers were downed on and isolated by the Muslims in general, because they were stipulated as astray and out of Islam. The conclusion of this writing is that although Ahmadiyya considered astray and infidel, but Ahmadiyya continues to grow and expands to all corners of the world, and now the movement is international. KEY WORDS: Mirza Ghulam Ahmad, Islam, Ahmadiyya community, revelation, astray, and infidel.About the Author: Kunto Sofianto, Ph.D. is a Senior Lecturer at the History Department, Faculty of Art and Humanities UNPAD (Padjadjaran University) Bandung, Jalan Raya Bandung-Sumedang Km.21, Jatinangor, Sumedang, West Java, Indonesia. For academic interests, the author is able to be reached via e-mail at: ksofianto@yahoo.comHow to cite this article? Sofianto, Kunto. (2016). âMirza Ghulam Ahmad: Founder of the Ahmadiyya Muslim from Qadian, Indiaâ in TAWARIKH: International Journal for Historical Studies, Vol.7(2) April, pp.183-200. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Chronicle of the article: Accepted (March 3, 2016); Revised (March 25, 2016); and Published (April 28, 2016).